Pembelajaran Bahasa Arab Melalui Metode Penerjemahan Arab-Indonesia Dalam Syair Syaikh Ahmad Bin Yahya An-Najmiy - Ahmad kirom; Siti ngaisah (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2023)
This study aims to describe and describe the techniques and methods of translating Arabic into Indonesian in Syaikh Ahmad Bin Yahya An-Najmiy's poetry. This research uses descriptive analysis method and qualitative approach. The source of the data in this study was a YouTube video with a duration of 1 minute 48 seconds from the "sharing information" channel with the title "Poems of Shaykh Ahmad Bin Yahya An Najmi Rahimahulloh about spending time with good deeds" and data in the form of Arabic poetry and translated sentences. by Al Ustadz Abu Amr Ridwan Al Ambooniy hafidzohulloh ta'ala. Based on the results of the analysis, 10 techniques were found out of a total of 50 techniques used by translators in 112 data, namely; literal (23), omission (8), inversion (4), natural borrowing (1), amplification (5), addition (3), adaptation (2), discursive creation (1), generalization (1), and conventional equivalence (2). The dominant technique applied is the addition technique, this is done to help convey the message or make it easier for the reader to understand. The translation method that tends to be applied by translators from the results of an analysis of the use of translation techniques and the type of text in the form of vocative is the communicative method.